(3OQQ GdYHGQGJ hZQQ GdETGQGJ aj JMbjb eYGfi GdGNJUGQGJs - (3CMeO Hf eMeO Hf eci GdMehis; (3GdMehj , CMeO Hf eMeO ecj, TgGH GdOjf CHh GdYHGS,J (B1098 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdHGMK hJMQjQgG gh Cf HYV GdENhI s
(3BNQgG (B:s
(3hGdNWjH Ohf GdScGci hgfG hba Gdbde s
(3Vef eLehY , JQJjHgG (B: 1s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B93s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B466s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs